2015
DOI: 10.1136/sextrans-2014-051790
|View full text |Cite
|
Sign up to set email alerts
|

UrogenitalChlamydia trachomatisstrain types, defined by high-resolution multilocus sequence typing, in relation to ethnicity and urogenital symptoms among a young screening population in Amsterdam, The Netherlands

Abstract: We found an association between urogenital C. trachomatis clusters and ethnicity among young screening participants in Amsterdam, the Netherlands. However, no association was found between C. trachomatis clusters and self-reported urogenital symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…For example, there were 109 samples from Europe, representing six different countries, and 19 (68%) of the 28 STs were novel. Our findings are similar to other studies in Europe where the rates for novel STs were 62% among high school students in Norway ( Gravningen et al, 2012 ), 65% among Tunisian sex workers ( Gharsallah et al, 2016 ) and 62% among young adults in Amsterdam ( Versteeg et al, 2015 ). Additional novel STs are likely to be identified as new regions undergo MLST.…”
Section: Discussionsupporting
confidence: 91%
“…For example, there were 109 samples from Europe, representing six different countries, and 19 (68%) of the 28 STs were novel. Our findings are similar to other studies in Europe where the rates for novel STs were 62% among high school students in Norway ( Gravningen et al, 2012 ), 65% among Tunisian sex workers ( Gharsallah et al, 2016 ) and 62% among young adults in Amsterdam ( Versteeg et al, 2015 ). Additional novel STs are likely to be identified as new regions undergo MLST.…”
Section: Discussionsupporting
confidence: 91%
“…Previous molecular epidemiological studies on Ct using MLST showed no association between Ct strain types and symptoms, anatomical locations, gender or geographical location. Most strain types were also globally distributed with similar ompA genovar distributions [ 10 , 61 63 ]. These studies therefore suggest that the population structure of Ct is comparable among different human populations and that the effect of selection bias would be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Both panels contained CT and LGV positives and for each panel 9 out of 10 original samples were still available for this study. In addition, a CT panel was used to test the sensitivity for a diverse set of urogenital genovar types, D to K [23]. In addition, a specificity panel consisting of 48 microbial species, including several Chlamydia non-trachoma species, was used to assess the specificity of the newly developed assay.…”
Section: Strategy Of the Studymentioning
confidence: 99%